Analisis Wacana Kritis Keputusan Pembubaran Front Pembela Islam di Kompas.com - Indah Suryawati; Jamalullail Jamalullail (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2021)
The government's decision regarding the dissolution and termination of all FPI activities raises pro and contra among the media and the public. The dissolution of FPI was decided by means of a decree signed by six ministers and heads of state institutions. This study aims to describe and dismantle the discourse of the news text on the decision to dissolve FPI using Critical Discourse Analysis (CDA). The research method used is Norman Fairclough's Critical Discourse Analysis through understanding text and context. There are five steps that are used as a reference. First, focus on social irregularities in its semiotic aspects. Second, identify barriers to address the social irregularities. Third, consider whether social order requires social irregularity. Fourth, identify possible ways to overcome these obstacles. Fifth, reflect critically from those four points. The results showed that kompas.com put FPI as the wrong position and the government's decision to dissolve FPI through an SKB was right. It is clear that kompas.com sided with the government. Kompas.com follows part of the flow of public votes in its news about FPI as a business strategy. The positioning of kompas.com was carried out because the government's decision to dissolve FPI caused pro and contra among the media and the public.